2012
DOI: 10.1007/s11274-011-0984-z
|View full text |Cite
|
Sign up to set email alerts
|

Human lactoferrin increases Helicobacter pylori internalisation into AGS cells

Abstract: Helicobacter pylori has high global infection rates and can cause other undesirable clinical manifestations such as duodenal ulcer (DU) and gastric cancer (GC). Frequencies of re-infection after therapeutic clearance and rates of DU versus GC vary geographically and differ markedly between developed and developing countries, which suggests additional factors may be involved. The possibility that, in vivo, lactoferrin (Lf) may play a subtle role in modulating micronutrient availability or bacterial internalisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…However, the observation of an infection-associated redistribution of the TfR receptor from the cytosol to the surface of AGS cells, coupled with an increase in transferrin uptake by infected MDCK cells [ 32 ] and a significant increase in ferritin-rich intracellular compartments in infected AGS cells (this study) strengthens the hypothesis that these bacteria have the potential to perturb cellular iron homeostasis. While they are normally considered non-invasive, the observation of that small numbers of bacteria are taken up and traffic to intracellular compartments inside AGS cells is in line with other studies [ 11 , 12 , 33 , 34 ]. Unrelated studies that demonstrate the presence of LAMP-1 [ 33 ] and absence of cathepsin D [ 34 ] in these bacteria-rich compartments, together with the finding that the bacteria-rich phagosomes are ferritin-rich, suggests they are likely to be post endosomal hybrids of late endosomes and lysosomes [ 35 ], an observation that is strengthened by the finding of internalised bacteria in acidic compartments, as evidenced by LysoTracker Red staining.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the observation of an infection-associated redistribution of the TfR receptor from the cytosol to the surface of AGS cells, coupled with an increase in transferrin uptake by infected MDCK cells [ 32 ] and a significant increase in ferritin-rich intracellular compartments in infected AGS cells (this study) strengthens the hypothesis that these bacteria have the potential to perturb cellular iron homeostasis. While they are normally considered non-invasive, the observation of that small numbers of bacteria are taken up and traffic to intracellular compartments inside AGS cells is in line with other studies [ 11 , 12 , 33 , 34 ]. Unrelated studies that demonstrate the presence of LAMP-1 [ 33 ] and absence of cathepsin D [ 34 ] in these bacteria-rich compartments, together with the finding that the bacteria-rich phagosomes are ferritin-rich, suggests they are likely to be post endosomal hybrids of late endosomes and lysosomes [ 35 ], an observation that is strengthened by the finding of internalised bacteria in acidic compartments, as evidenced by LysoTracker Red staining.…”
Section: Discussionsupporting
confidence: 84%
“…Although largely non-invasive, a growing number of studies provide evidence that H . pylori can enter gastric epithelial cells in vivo [ 10 ] and in vitro [ 11 , 12 ], albeit at very low frequencies. There is also evidence that the number of bacteria entering the cells increases when the extracellular environment doesn’t support bacterial growth [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using TEM and immunohistochemistry (IHC) technique, some researchers found that H. pylori, in specimens including gastritis, peptic ulcer, precancerosis and gastric cancer, can invade into epithelial cells and even lamina propria in gastric mucosa (Dubois & Borén, 2007;Ozbek et al, 2010). By immunofluorescence (IF) technique, internalized H. pylori was observed in AGS cells (Amieva et al, 2002;Chu et al, 2010;Coray et al, 2012;Kwok et al, 2002). Other studies verified that H. pylori can enter into AGS, MKN45, Huh7, HEp-2, HeLa and so on, and noted that invasive capability was not similar according to different host cells (Dubois & Borén, 2007;Ito et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The role of Lf is to sequester iron at mucosal surfaces, thus reducing its availability to bacteria (Alexander et al 2012), whereas ferritin is an iron-storage protein whose expression is increased in response to high levels of iron and/or inflammation (Alkhateeb et al 2013). There is evidence of Lf-associated internalisation of H. pylori into gastric epithelial cells (Coray et al 2012) and increased Lf expression is seen in gastric tissue from patients infected with H. pylori (Dogan et al 2012). To date, there are no reports of an H. pylori-associated change in ferritin levels in the human stomach, but an increase in cytosolic ferric iron is observed when a human gastric epithelial cell line is exposed to outer membrane vesicles constitutively shed from the surface of these bacteria (Chitcholtan et al 2008).…”
Section: Introductionmentioning
confidence: 99%